Binusmaya sebagai Sumber Materi dalam Pembelajaran Berbasis E-Learning - Suparto Darudiato; Kadek Iran Wibowo (ComTech: Computer, Mathematics and Engineering Applications, 2013)
E-learning is a media that used in order to help learning process. This paper aims to determine the components that support Binusmaya to become one of e-learning media. It also describes the benefits that can be provided by binusmaya as a learning media. Additionally, this paper analysis the constraints that must beconsidered in implementing Binusmaya so that it can give benefit optimally. Data and information used in this paper are obtained from several books, website, journal and questionnaires related with topic. The result from this paper is expected to provide information and knowledge about binusmaya as a learning media based elearning.